A taxonomic monograph of subfamily Scolytinae (Coleoptera: Curculionidae) in the Western Himalaya - Buhroo, Abdul Ahad; Zubair, R. M. (Zootaxa, 2024)
We investigated the scolytine fauna of the West Himalayan region of India. The present study combines field samples, museum specimens, and published data to catalog the scolytine diversity. We recognize 57 scolytine species from 15 tribes and 25 genera. Five new species Cryphalus himalayensis sp. nov., Dryocoetes asperatus sp. nov., Ernoporus squamosus sp. nov., Scolytoplatypus denticauda sp. nov., and Hypothenemus ficivorus sp. nov. are described from the region. Previously reported and inadequately characterized species are imaged and redescribed. Two new Indian records, seven new regional records, and fifteen new host records are reported. Keys to genera and photographs of each species are provided to facilitate identification. Mitochondrial COX-1 sequences were generated from some Himalayan species and sequences from GenBank were utilized for comparison with other related species. The current monographic study includes an overview of each species' taxonomic diagnosis, range, and host plants. Furthermore, an updated list of 165 scolytine species, distributed in the Himalaya but excluding its eastern part of Arunachal Pradesh, is also provided.